2019
DOI: 10.1016/j.aap.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

How much space do drivers provide when passing cyclists? Understanding the impact of motor vehicle and infrastructure characteristics on passing distance

Abstract: How much space do drivers provide when passing cyclists? Understanding the impact of motor vehicle and infrastructure characteristics on passing distance. Accident Analysis & Prevention

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
4
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 26 publications
2
51
4
4
Order By: Relevance
“…"Dooring" injuries were found to be infrequent for cyclists in the present cohort, which is consistent with previous studies in Australia [12,38]. However, we recognise that cyclists may avoid dooring injuries by riding closer to traffic on roads with parked cars than they do on roads without parked cars [39]. Road safety may be enhanced with traffic calming strategies to reduce traffic volume and speed near intersections and collision hotspots for road users faced with turning or merging traffic, especially cyclists [34].…”
Section: Implications For Road Safetysupporting
confidence: 92%
“…"Dooring" injuries were found to be infrequent for cyclists in the present cohort, which is consistent with previous studies in Australia [12,38]. However, we recognise that cyclists may avoid dooring injuries by riding closer to traffic on roads with parked cars than they do on roads without parked cars [39]. Road safety may be enhanced with traffic calming strategies to reduce traffic volume and speed near intersections and collision hotspots for road users faced with turning or merging traffic, especially cyclists [34].…”
Section: Implications For Road Safetysupporting
confidence: 92%
“…Therefore, it would be preferable to place less emphasis on the development of bike lanes and shared bike lanes. It has also been widely shown that the risks of accidents involving cyclists are greater on these types of bike lanes because cyclists share the road with motor vehicles [48,49]. Therefore, cyclists' exposure to noise is an important issue in Montreal and Paris that might discourage bicycle use.…”
Section: Implications For Policymentioning
confidence: 99%
“…Cyclist overtaking maneuvers can be split into four phases [6], [27], [30], which may help to prioritize and develop safety systems that support the driver in reducing crash risks in those phases: 1) approaching phase: when the ego vehicle approaches the cyclist, and the driver has to decide between a flying or an accelerative maneuver, 2) steering away phase: when the driver steers away to achieve a lateral distance to the cyclist, 3) passing phase: when the ego vehicle passes the cyclist while driving in parallel, 4) returning phase: when the driver has passed the cyclist and steers back into the lane. Several recent studies investigated driver behavior in these phases by leveraging different test environments: simulator studies [31], [32], test-track studies [30], [33], field test studies [27] and naturalistic driving studies [6], [34]- [36]. While simulator and test-track studies have lower ecological validity than field tests or naturalistic driving studies, they can offer more controlled data with higher resolution, which facilitates the development of predictive driver models [5].…”
Section: Existing Research On Driver-cyclist Interaction In Overtamentioning
confidence: 99%